Low Mortality of Staphylococcus aureus Bacteremia in Icelandic Children: Nationwide Study on Incidence and Outcome. - Asgeirsson, Hilmir; Gudlaugsson, Olafur; Kristinsson, Karl G; Vilbergsson, Gauti R; Heiddal, Sigurdur; Haraldsson, Asgeir; Weiland, Ola; Kristjansson, Mar (Pediatric Infectious Disease Journal, 2015)
To access publisher's full text version of this article click on the hyperlink at the bottom of the page Staphylococcus aureus is a major cause of blood stream infections, but population-based studies on pediatric S. aureus bacteremia (SAB) are sparse. The objective of the study was to evaluate the incidence and mortality of SAB in Icelandic children over time, and to assess the proportions of nosocomial and health-care-associated infections. Children <18 years with positive blood cultures for S. aureus from January 1995 through December 2011 were identified retrospectively at the clinical microbiology laboratories performing blood cultures in Iceland. Clinical data were collected from medical records. In total, 140 children had 146 distinct episodes of SAB. Bacteremia-related mortality was 0.7% (1/146), all-cause 30-day mortality, 1.4% (2/146), and 1-year mortality, 3.6% (5/140). The annual incidence of SAB was 10.9/100,000 children, decreasing by 36% from 13.1/100,000 in 1995-2003 to 8.4/100,000 in 2004-2011 (P < 0.001). At the same time the annual number of blood cultures analyzed at the main study site decreased from 1529 to 1143 (25%). SAB incidence was highest in infants (<1 year), 58.8/100,000. Of 146 episodes 50 (34%) were nosocomial, 21 (14%) health-care associated and 75 (51%) community acquired. No methicillin-resistant S. aureus isolate was identified. In this nationwide study on pediatric SAB, the case fatality ratio was very low. A decreasing incidence was seen, possibly related to fewer blood cultures being collected. Nosocomial and health-care-associated infections accounted for 50% of the cases. The findings provide useful information on the epidemiology and outcome of SAB in children.